Sestrin2 facilitates glutamine‐dependent transcription of PGC‐1α and survival of liver cancer cells under glucose limitation. (8th March 2018) - Kumar, Ashish; Giri, Sagnik; Shaha, Chandrima
Abstract : Differential utilization of metabolites and metabolic plasticity can confer adaptation to cancer cells under metabolic stress. Glutamine is one of the vital and versatile nutrients that cancer cells consume avidly for their proliferation, and therefore mechanisms related to glutamine metabolism have been identified as targets. Recently, sestrin2 ( SESN2 ), a stress‐inducible protein, has been reported to regulate survival in glutamine‐depleted cancer cells; based on this, we explored if SESN2 could regulate glutamine metabolism during glucose starvation. This report highlights the role of SESN2 in the regulation of glutamine‐dependent activation of the mitochondrial biogenesis marker peroxisome proliferator‐activated receptor γ coactivator 1α (PGC‐1α) under glucose scarcity in liver cancer cells (HepG2). We demonstrate that down‐regulation of SESN2 induces a decrease in the levels of intracellular glutamine and PGC‐1α under glucose deprivation, concomitant with a decline in cell survival, but no effect was observed on the invasive or migration potential of the cells. Under similar metabolic conditions, SESN2 forms a complex with c‐Jun N‐terminal kinase (JNK) and forkhead box protein O1 (FOXO1). Absence of SESN2 or inhibition of JNK reduces nuclear translocation of FOXO1, consequently causing transcriptional inhibition of PGC‐1α. Notably, our observations demonstrate a reduction in cell viability under high glutamine and low glucose conditions during SESN2 down‐regulation that could be rescued on JNK inhibition. To recover from acetaminophen‐induced mitochondrial damage, SESN2 was crucial for glutamine‐mediated activation of PGC‐1α in HepG2 cells. Collectively, we demonstrate a novel role of SESN2 in mediating activation of PGC‐1α by modulating glutamine metabolism that facilitates cancer cell survival under glucose‐limited metabolic conditions. Abstract : This study demonstrates that Sestrin2, a stress‐inducible protein, facilitates a metabolic rewiring process that promotes mitochondrial biogenesis and cancer cell survival under glucose limitation. Sestrin2 activation under glucose‐limited and glutamine‐adequate conditions results in JNK‐dependent nuclear migration of FOXO1 leading to transcriptional activation of PGC‐1α (a mitochondrial biogenesis marker).